ANALYSIS OF PROBLEM-SOLVING ABILITY BASED ON STUDENT GENDER - Fera Juwita; Venty Meilasari (Universitas Muhammadiyah Lampung, 2025)
Abstract Problem-solving skills are important for students to be able to overcome problems in mathematics and everyday life. However, 12th grade students at SMK Negeri 2 Kotabumi still lack adequate problem-solving skills. This study aims to explain how male and female students solve problems in statistics with the topic of single data mean at SMK Negeri 2 Kotabumi. This study employs a descriptive qualitative method. The research subjects consist of two male students and two female students in the 12th grade of the Computer Networking Technology program, selected using purposive sampling. The research instruments include the researcher themselves, a test instrument, and an interview guide. Data collection methods included tests and interviews. To verify data validity, triangulation of time, research persistence, and member checks were used. Data analysis methods included data reduction, data presentation, and conclusion drawing. The results of this study indicate that male students successfully completed each stage of problem-solving according to Polya. The process begins with understanding the problem, formulating a solution plan, implementing the plan, and finally checking the answer. Female students successfully carried out three of the four problem-solving stages according to Polya, namely understanding the problem, designing a solution, and implementing the plan. However, in the stage of checking the answer, female students often skipped this step.